The Concept of Spending in The General Economy of Georges Bataille: Social Crisis Between Espenditure and Abundance - Pavle Milenković; Alpar Lošonc (Etnoantropološki Problemi)
This paper actualizes the conceptual pair scarcity-abundance through the phenomenon of spending surpluses as the accursed share (la part maudite) in the field of ethnology, sociology and philosophy of Georges Bataille. Within his unfinished project of general economy, and in dialogue with the same conceptual pair in the field of economic theory, particularly in the political economy of Lionel Robbins and J. M. Keynes, this study opens a space for both assessing the relevance of Bataille's insights in the contemporary moment of neoliberal capitalism and for reconsidering the status of scarcity and abundance within the polycrisis of late capitalism. The fluctuation of these concepts and categories serves as a template for understanding shifts in the discourse of economic theory as well as social theory in a broader sense, from classical political economy to economic neoclassical theory and neoliberalism during the twentieth century and up to the present day. Bataille's complex and controversial body of work, marked by a transgressive synthesis of sociology, anthropology, philosophy and literature continues to inspire critical reflections on the neoliberal phase of modernity.